(untitled) (Journal of Plant Disease Sciences, 2026)
Strawberry is a highly perishable fruit and is highly susceptible to pathogenic fungi, resulting in significant nutritional and economic losses. In this study, healthy and infected strawberry fruits were collected during March and April of 2024 and 2025 from different markets of Alipurduar, West Bengal, India. Soft rot was identified as a common postharvest disease caused by Rhizopus stolonifer, which was confirmed through microscopic examination of the isolated fungus and rDNA ITS sequencing. Pathogenicity was further verified by inoculating healthy fruits and re-isolating the pathogen. As an alternative to chemical fungicides, sustainable management strategies were evaluated using four Trichoderma species (T. harzianum, T. koningiopsis, T. virens, and one unidentified Trichoderma species) along with six essential oils against R. stolonifer. All Trichoderma isolates inhibited pathogen growth, with T. harzianum and T. virens showing the greatest effectiveness when inoculated one or two days before the pathogen. Among the six essential oils tested, cinnamon, citronella, and clove oils completely inhibited pathogen growth in vitro even after 17 days of incubation. Application of these essential oils on strawberry fruits also reduced disease development, with cinnamon oil showing the highest level of inhibition, followed by citronella and clove oils. These findings indicate that selected Trichoderma species and essential oils have considerable potential as eco-friendly alternatives for the sustainable management of postharvest soft rot of strawberry caused by Rhizopus stolonifer.